Congenital central hypoventilation syndrome associated with Hirschsprung's Disease: case report and literature review - Renata Lazari Sandoval; Carlos Moreno Zaconeta; Paulo Roberto Margotto; Maria Teresinha de Oliveira Cardoso; Evely Mirella Santos França; Cristina Touguinha Neves Medina; Talyta Matos Canó; Aline Saliba de Faria
Abstract Objective: To report the case of a newborn with recurrent episodes of apnea, diagnosed with Congenital Central hypoventilation syndrome (CCHS) associated with Hirschsprung's disease (HD), configuring Haddad syndrome. Case description: Third child born at full-term to a non-consanguineous couple through normal delivery without complications, with appropriate weight and length for gestational age. Soon after birth he started to show bradypnea, bradycardia and cyanosis, being submitted to tracheal intubation and started empiric antibiotic therapy for suspected early neonatal sepsis. During hospitalization in the NICU, he showed difficulty to undergo extubation due to episodes of desaturation during sleep and wakefulness. He had recurrent episodes of hypoglycemia, hyperglycemia, metabolic acidosis, abdominal distension, leukocytosis, increase in C-reactive protein levels, with negative blood cultures and suspected inborn error of metabolism. At 2 months of age he was diagnosed with long-segment Hirschsprung's disease and was submitted to segment resection and colostomy through Hartmann's procedure. A genetic research was performed by polymerase chain reaction for CCHS screening, which showed the mutated allele of PHOX2B gene, confirming the diagnosis. Comments: This is a rare genetic, autosomal dominant disease, caused by mutation in PHOX2B gene, located in chromosome band 4p12, which results in autonomic nervous system dysfunction. CCHS can also occur with Hirschsprung's disease and tumors derived from the neural crest. There is a correlation between phenotype and genotype, as well as high intrafamilial phenotypic variability. In the neonatal period it can simulate cases of sepsis and inborn errors of metabolism.